1988
DOI: 10.1017/s0031182000058789
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of enhanced malaria transmission and host bias induced by modified vector blood location behaviour

Abstract: Monte Carlo simulations were developed to assess the potential impact of parasite pathology on vector salivary function as well as of host haemostasis on transmission. Assuming that a proportion of desisting vectors switch host following failure to locate blood, we demonstrate three possible consequences: (1) infected vectors contact more hosts than non-infected host, (2) non-infected vectors are biased to infected hosts, independently of attraction, and (3) an exponential relationship exists between parasite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Hitherto, it is the influence of vector-parasite interactions on the values of the ratios L/L, a/a and a'/a" that have been the concern, implicitly or explicitly, of experimentalists (Table 1, column 4) and theoreticians (Anderson, 1981 ;Ribeiro, Rossignol & Spielman, 1985;Kingsolver, 1987;Dobson, 1988;Rossignol & Rossignol, 1988) alike. Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto, it is the influence of vector-parasite interactions on the values of the ratios L/L, a/a and a'/a" that have been the concern, implicitly or explicitly, of experimentalists (Table 1, column 4) and theoreticians (Anderson, 1981 ;Ribeiro, Rossignol & Spielman, 1985;Kingsolver, 1987;Dobson, 1988;Rossignol & Rossignol, 1988) alike. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the epidemiological significance of parasite-induced effects, both experimentalists (Table 1) and theoreticians (Anderson, 1981;Ribeiro, Rossignol & Spielman, 1985;Kingsolver, 1987;Dobson, 1988;Rossignol & Rossignol, 1988) have generally compared infected with uninfected vectors, and concluded that parasites either increase or decrease the rate of transmission. However, this is not the most relevant comparison in practical epidemiology because parasites are just one of a number of sources of measurement bias.…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism underlying these changes in feeding behavior is suggested by data demonstrating that salivary gland sporozoites decrease the level of apyrase in the mosquito host's saliva, making it more difficult for them to feed to repletion on one host [96,97]. It is predicted that such changes in feeding behavior would significantly increase the likelihood that a single infected mosquito transmits sporozoites [98,99].…”
Section: Does Plasmodium Manipulate Its Mosquito Host To Increase Transmission Likelihood?mentioning
confidence: 99%
“…Anaplasma modulates the immune response of ticks, but it does not affect the feeding behaviour, which helps to maintain the vector capacity [93]. However, there is a need for more work to be done on feeding and other ticks' behaviours.…”
Section: Changes In Blood Feedingmentioning
confidence: 99%